2007
DOI: 10.1080/10503300600812775
|View full text |Cite
|
Sign up to set email alerts
|

Culture and the therapeutic relationship: Perspectives from Chinese clients

Abstract: Culture and therapy 2 Culture and the therapeutic relationship: Perspectives from Chinese clients AbstractChinese people in the UK and USA underutilise mental health services and, when they do seek help, may find that therapy does not meet their needs. In response to calls in the literature for naturalistic studies of therapy with people of Chinese background, this study used a qualitative, multiple case approach to examine clients' individual experiences in depth and detail. Semi-structured interviews were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 29 publications
2
23
0
1
Order By: Relevance
“…In 2007, this journal published at least five studies with client experiences of therapy as a key element (Fitzpatrick & Chamodraka, 2007;Jim & Pistrang, 2007;Nilsson et al, 2007;Ramnerš & …st, 2007;Vanaerschot & Lietaer, 2007); most of these used qualitative or mixed methods. In addition, Psychotherapy Research has also recently published a qualitative meta-synthesis of a subset of this recent literature, client experiences of the impacts of helpful significant therapy events (Timulak, 2007).…”
mentioning
confidence: 99%
“…In 2007, this journal published at least five studies with client experiences of therapy as a key element (Fitzpatrick & Chamodraka, 2007;Jim & Pistrang, 2007;Nilsson et al, 2007;Ramnerš & …st, 2007;Vanaerschot & Lietaer, 2007); most of these used qualitative or mixed methods. In addition, Psychotherapy Research has also recently published a qualitative meta-synthesis of a subset of this recent literature, client experiences of the impacts of helpful significant therapy events (Timulak, 2007).…”
mentioning
confidence: 99%
“…En este campo, durante los últimos años se ha incrementado la investigación cualitativa centrada en la experiencia subjetiva de los pacientes como un elemento clave para la evaluación de los procesos y resultados de la psicoterapia (Berg, Raminani, Greer, Harwood & Safren, 2008;Connolly & Strupp, 1996 ;Fitzpatrick & Chamodraka, 2007;Henretty, Levitt & Mathews, 2008;Israel, Gorcheva, Burnes & Walther, 2008;Jim & Pistrang, 2007;Mörtl & Von Wietersheim, 2008;Nilsson, Sensson, Sandell & Clinton, 2007;Pattee & Farber, 2008;Ramnerö & Öst, 2007;Silverstein, Auerbach & Levant, 2006;Vanaerschot & Lietaer, 2007;Williams & Levitt, 2008). Estos estudios han intentado analizar en qué medida la representación del paciente del proceso de cambio y sus resultados es relevante para una mejor comprensión de los mismos.…”
Section: Introductionunclassified
“…A study involved Chinese people using counselling services in the UK revealed that the provision of such an environment was vital to all participants in a therapeutic relationship so that they felt at ease to ventilate their inner feelings and conflicts (Jim and Pistrang's, 2007). Other studies also show that establishing ground rules is crucial to facilitate and support service users to share and disclose their vulnerabilities in educational settings (Frisby, 2001;Hayward, et al 2005).…”
Section: Strategies To Develop a Trusting Relationship With Chinese Smentioning
confidence: 99%
“…This observation confirms that Chinese service users and carers often perceive clinicians / academics to be authoritative experts. They tend to adopt the role as students in a therapeutic relationship and view the clinicians as teachers (Jim and Pistrang, 2007). As the counselling sessions take place on the premises of the University of Hong Kong, an educational institution, viewing the clinician as an authoritative expert helps the couple settle more readily in a culturally familiar social role (Lin et al, 1995).…”
Section: Trust To Get Involvedmentioning
confidence: 99%
See 1 more Smart Citation